2016
DOI: 10.1007/s12603-015-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of food-based fortification in older people a systematic review and meta-analysis

Abstract: Despite the limited evidence, due to their simplicity, low cost, and positive results in protein and calories intake, simple dietary interventions based on the food-based fortification or densification with protein or energy of the standard diet could be considered in patients at risk of malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 22 publications
1
61
0
Order By: Relevance
“…In general, protein-containing supplements result in small improvements in outcomes that are more marked when combined with programs of rehabilitation/physical activity (82). In malnourished or undernourished patients, some outcomes are improved, and meta-analyses have shown (84, 85) improved nutritional status. The interventions used in the trials (84, 85) aimed to provide between 175 additional kcal/day and up to a maximum of 1,350 additional kcal/day.…”
Section: Pressure Ulcers and Acute And Chronic Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, protein-containing supplements result in small improvements in outcomes that are more marked when combined with programs of rehabilitation/physical activity (82). In malnourished or undernourished patients, some outcomes are improved, and meta-analyses have shown (84, 85) improved nutritional status. The interventions used in the trials (84, 85) aimed to provide between 175 additional kcal/day and up to a maximum of 1,350 additional kcal/day.…”
Section: Pressure Ulcers and Acute And Chronic Illnessmentioning
confidence: 99%
“…In malnourished or undernourished patients, some outcomes are improved, and meta-analyses have shown (84, 85) improved nutritional status. The interventions used in the trials (84, 85) aimed to provide between 175 additional kcal/day and up to a maximum of 1,350 additional kcal/day. Additional protein was between 10 and 50 g protein/day (84, 85).…”
Section: Pressure Ulcers and Acute And Chronic Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the results was member checked and quotes typical of the themes and subthemes identified for reporting. Qualitative methods were used to gain an in‐depth understanding of the meaningfulness of the program, what needed improving and the feasibility of making changes in the workplace . Results from the questionnaires, focus groups and individual interviews were triangulated to identify consistent responses and to gain a clearer understanding .…”
Section: Methodsmentioning
confidence: 99%
“…13 Meta-analysis (4 studies) demonstrated that food fortification advice increased the consumption of energy (200kcal/day, 95% CI 133 to 267; p<0.00001) and protein (7g/day, 95% CI 1 to 13; p<0.00001). 13 However, the authors noted that most studies were of poor methodological quality.…”
Section: Dietary Advice and Food Fortificationmentioning
confidence: 99%